Allergic reactions and antiasparaginase antibodies in children with high‐risk acute lymphoblastic leukemia: A children's oncology group report. Issue 23 (26th August 2015) - Ko, Richard H.; Jones, Tamekia L.; Radvinsky, David; Robison, Nathan; Gaynon, Paul S.; Panosyan, Eduard H.; Avramis, Ioannis A.; Avramis, Vassilios I.; Rubin, Joan; Ettinger, Lawrence J.; Seibel, Nita L.; Dhall, Girish
Abstract : BACKGROUND: The objectives of this study were to assess the incidence of clinical allergy and end‐induction antiasparaginase (anti‐ASNase) antibodies in children with high‐risk acute lymphoblastic leukemia treated with pegylated (PEG) Escherichia coli ASNase and to determine whether they carry any prognostic significance. METHODS: Of 2057 eligible patients, 1155 were allocated to augmented arms in which PEG ASNase replaced native ASNase postinduction. Erwinia chrysanthemi ( Erwinia ) ASNase could be used to replace native ASNase after allergy, if available. Allergy and survival data were complete for 990 patients. End‐induction antibody titers were available for 600 patients. RESULTS: During the consolidation phase, 289 of 990 patients (29.2%) had an allergic reaction. There were fewer allergic reactions to Erwinia ASNase than to native ASNase (odds ratio, 4.33; P  < .0001) or PEG ASNase (odds ratio, 3.08; P  < .0001) only during phase 1 of interim maintenance. There was no significant difference in 5‐year event‐free survival (EFS) between patients who received PEG ASNase throughout the entire study postinduction versus those who developed an allergic reaction to PEG ASNase during consolidation phase and subsequently received Erwinia ASNase (80.8% ± 2.8% and 81.6% ± 3.8%, respectively; P  = .66). Patients who had positive antibody titers postinduction were more likely to have an allergic reaction to PEG ASNase (odds ratio, 2.4; P  < .001). The 5‐year EFS rate between patients who had negative versus positive antibody titers (80% ± 2.6% and 77.7% ± 4.3%, respectively; P  = .68) and between patients who did not receive any ASNase postconsolidation and those who received PEG ASNase throughout the study ( P  = .22) were significantly different. CONCLUSIONS: The current results demonstrate differences in the incidence rates of toxicity between ASNase preparations but not in EFS. The presence of anti‐ASNase antibodies did not affect EFS. Cancer 2015;121:4205–4211. © 2015 American Cancer Society . Abstract : Different preparations of asparaginase are used in the treatment of pediatric acute lymphoblastic leukemia, and the optimal use of this agent has yet to be elucidated. The authors observe differences in the incidence of toxicity with various asparaginase preparations and demonstrate that antiasparaginase antibodies do not affect event‐free survival.